Penerapan Sifat Kamalullah Dalam Puisi Sufistik Taman Taqwa (Sains Humanika, 2018)
This article was carried out to identify and to analyse the concept of Kamalullah in the collection of poems by Suhaimi Haji Muhammad that utilises the concept of Kamal within the theory of Takmilah. The study focused on the collection of poems entitled Taman Takwa that involved 79 titles related to divinity. The study was qualitatively analysed by implementing subjective statistical evidences. The secondary data were collected based on library research. The result of the study shows that the aspect of Kamalullah whether in the form of ma'ani (attributes that Allah has to show His perfection) or maknawi (attributes that Allah possesses) was successfully conceptualized by the poet. With reference to the 504 words and the adage of Kamalullah, were classified within the attribute of Qudrah, Iradah, Qaunuhu Sami'an, Sama’ and Mukhalafatuhu lil Hawadith. From the data, the poet wanted to emphasize on the ma'ani approach as compared to the maknawi approach through his poetry in delivering the atrributes of Kamalullah to the readers. This article concluded that muslim poets are responsible to preach to the society in understanding the concept and the discourse of Kamalullah by utilising their talent, creativity and also wisdom in the poetry creation.
Keywords: Kamalullah; takmilah theory; poem; divinity; creativity